Shortcut to Rebuilding Public Trust: Fact-Checking Journalism by YNA in South Korea - Ha, Jae Sik (Department of Communications, Universitas Islam Indonesia, 2024)
This study investigated how the emergence and practice of a fact-checking movement in South Korea have assisted the revival of journalism with a primary focus on truth-seeking and information verification. It examined in what ways Yonhap News Agency (YNA), a leading news agency in South Korea, fact-checked social and political issues, as well as the COVID-19 pandemic. This study employed in-depth interviews with fact-checking journalists at YNA. In addition to that, to trace YNA’s fact-checking activities and cross-check the findings from the interviews, this study conducted textual analysis of YNA’s fact-checking articles, examining their claims, evidence, and judgments. This study found that YNA’s fact-checking services contributed to preventing the spread of the ‘infodemic’ in South Korea. YNA’s fact-checking journalism can be considered as one form of ethical journalism that ensured incorrect information did not pass through journalistic gates in the pre-internet era. This study underscores the significance of fact-checking journalism in enhancing the quality of journalism worldwide.